Determinants of the Continuum of Maternal Healthcare Services in Northwest Ethiopia: Findings from the Primary Health Care Project. (26th August 2020) - Atnafu, Asmamaw; Kebede, Adane; Misganaw, Bisrat; Teshome, Destaw Fetene; Biks, Gashaw Andargie; Demissie, Getu Debalkie; Wolde, Haileab Fekadu; Gelaye, Kassahun Alemu; Yitayal, Mezgebu; Ayele, Tadesse Awoke; Azale, Telake; Derso, Terefe; et al.
Abstract : Background . The maternity continuum of care is the continuity of maternal healthcare services that a woman uses, which includes antenatal care (ANC 4+), skill birth attendant (SBA), and postnatal care (PNC) within 48 hours of delivery. It is one of the essential strategies for reducing maternal and newborn mortality. This study aimed to assess the factors associated with the completion of a continuum of maternal healthcare services among mothers who gave birth in the past five years. Methods . A community-based cross-sectional study was conducted from May 01 to June 29, 2019, among 565 randomly selected mothers who gave birth in five years before the study in primary healthcare project implementation districts of north Gondar zone, Amhara National Regional State, Ethiopia. Bivariable and multivariable logistic regression analysis were computed, and in the multivariable logistic regression analysis, adjusted odds ratio (AOR) with 95% confidence interval (CI) and a p value of less than 0.05 were used to identify the associated factors with completion of the continuum of maternal healthcare services. Results . The study revealed that the overall completion of the continuum of maternal healthcare services was 21.60% (95% CI: 18.20, 24.90). Women who were able to read and write (AOR: 2.70, 95% CI: 1.22, 6.04), using car/motorcycle as a means of transportation to get the health facility (AOR: 5.59, 95% CI: 2.29, 9.50), travel time less than an hour to get the health facility (AOR: 4.98, 95% CI: 2.97, 8.38), being satisfied with the service delivery (AOR: 1.89, 95% CI: 1.15, 3.11), and getting health education on maternal healthcare services in the last 6 months (AOR: 2.77, 95% CI: 1.52, 5.05) were factors associated with the completion of the continuum of maternal healthcare services. Conclusions . The completion of the continuum of maternal healthcare services was relatively low, indicating that women were not getting the likely health benefit from the present health services. Therefore, interventions should focus on increasing women's awareness, improving the availability of services at nearby health facilities, and improving service delivery by considering women's preferences and needs to increase their satisfaction are essential to increase the completion of maternal healthcare services.